Upaya Peningkatan Kepuasan Kerja Anggota Kepolisian Melalui Pemenuhan Kebutuhan dan Kompensasi - Noermijati -; Ristri O. (Jurnal Aplikasi Manajemen, 2012)
﻿The objectives of this research is to analyze the effects of needs and compensations fulfillment on police department (Satreskrim) members job satisfaction. Satreskrim is demanded to always give proper and satisfying service to the society. In increasing service or productive and professional performance, members job satisfaction needs to be fulfilled. This research is a combination of explanatory research, which emphasize the connection between research variables and tests the formulated hypothesis and descriptive research as a next step after explanatory research, which discovers and portrays how big the effect of these variables. The population in this research is Satuan Reserse Kriminal Polres Kota X. Samples are chosen using proportional random sampling method, based on position level. Data collection is using questionnare, interview, observation and documentation. multiple regression analysis is used to process the data. The result of this research shows that needs fulfillment and compensations affects job satisfaction simultaneously. Partially, needs fulfillment doesn’t affect job satisfaction. Whereas, compensations partially affects job satisfaction . Compensations has dominant effect on job satisfaction. Based on the result, researcher needs to suggest the Indonesian Police Department to increase members job satisfaction continuously , so that they will be able to encourage better and professional job performance.Keyword : needs fulfillment, ERG Alderfer, compensation, job satisfaction, police department.